A review on the recent developments in modeling heat and material transfer characteristics during welding. (2020) - Dhinakaran, V.; Varsha Shree, M.; Jagadeesha, T.; Bupathi Ram, P.M.; Sathish, T.; Stalin, B.
Abstract: The scope of this paper is to provide a thorough understanding of the current level of research expertise in modeling the heat transfer and material transfer characteristics during various types of welding, based on a literature review of research endured in this field. Initially, an overview of the different heat source models available to explain the energy distribution during welding is reviewed. Based on these heat source models, various temperature and flow models were developed for the individual applications of welding. Publications associated with the modeling of heat and material transfer characteristics are discussed extensively by studying the mechanics of weld formation, the physics involved, the modeling approach and constraints. A comparison is made with different models that were developed and the extent to which the models have evolved from their early stages through a better understanding of the physics involved during welding is highlighted. The need to further develop models for problems of specific nature is emphasized, the reference for researchers willing to work on this field and the scope for future work are discussed before concluding the subject.